Materials characterization by Auger electron spectroscopy sputter depth profiling - Zalar, Anton (Informacije MIDEM, 2000)
Depth profiling by ion sputtering in combination with Auger electron spectroscopy (AES) has become a valuable analytical tool in microelectronics and those areas of research and technology where the chemical composition of surfaces, interfaces and thin films is of importance. Its application range from fundamental surface and interface studies to thin-film structures for electronic and microelectronic devices, wear- and corrosion-resistant coatings, surfaces modified by plasma technique or ion implantation, etc. Reactions at surfaces as well as resulting electrical and mechanical properties can only be understood if the relevant chemical and structural changes in the investigated thin-film structures are known. This requires a quantitative spatially resolved analysis and in-depth distribution of chemical composition with a high depth distribution of chemical composition with a high depth resolution. However, ion sputtering is not an ideal layer-by-layer erosion but is a result of a complex ion beam-sample interaction proacess. Various phenomena, the most important of which are due to ion beam induced changes of surface roughness and composition, limit the experimentally achievable resolution. The principles of the method and its fundamental capabilities and limitations will be discussed. The applicability of the AES depth profiling in microelectronics and some other technical fields will be illustrated by depth profiles of the characteristic samples.
Keywords: AES; Augerjeva spektroskopija; karakterizacija materialov; naprševanje; polprevodniki; tanke plasti